Clinical outcomes of clear lens extraction in eyes with primary angle closure. Issue 7 (July 2015) - Dada, Tanuj; Rathi, Anubha; Angmo, Dewang; Agarwal, Tushar; Vanathi, Murugesan; Khokhar, Sudarshan K.; Vajpayee, Rasik B.
Abstract : Purpose : To evaluate the effect of clear lens extraction (CLE) on intraocular pressure (IOP) and the anterior chamber angle in primary angle closure after laser peripheral iridotomy (LPI). Setting : Tertiary eyecare center at a university hospital, New Delhi, India. Design : Prospective case series. Methods : The study included eyes with primary angle closure and an IOP over 25.0 mm Hg more than 8 weeks after LPI. All eyes had CLE by phacoemulsification. Absolute success was defined as an IOP less than 18.0 mm Hg without medications at 12 months. Results : In 44 eyes (24 women, 20 men; mean age 57.2 years ± 4.2 [SD]), the mean preoperative IOP of 27.1 ± 1.55 mm Hg decreased to 13.2 ± 1.12 mm Hg at 12 months ( P < .0001). The angle opening distance at 500 μm increased from baseline values at 0 degrees (from 0.104 ± 0.015 mm to 0.31 ± 0.013 mm) and 180 degrees (from 0.202 ± 0.008 mm to 0.412 ± 0.012 mm). The trabecular iris angle also increased at 0 degrees (from 9.3 ± 3.2 degrees to 32.7 ± 5.6 degrees) and 180 degrees (from 9.12 ± 3.2 degrees to 31.7 ± 5.6 degrees) (all P < .0001). In multivariate analysis, the preoperative IOP was the strongest determinant of IOP change ( R 2 = 0.69, P < .0001). Absolute success was achieved in 38 eyes (86.3%). Conclusion : Clear lens extraction led to a significant reduction in IOP, a widening of the anterior chamber angle, and a reduced need for ocular hypotensive medications in eyes with primary angle closure and persistently raised IOP after LPI. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.